The squat jump and sprint force-velocity profiles of elite female football players are not influenced by the menstrual cycle phases and oral contraceptive use - Bouvier, J.; Igonin, P.-H.; Boithias, M.; Fouré, A.; Belli, A.; Boisseau, N.; Martin, C. (European Journal of Applied Physiology, 2025)
Purpose Force-velocity profiling is an excellent tool for training individualization, especially in sports with well-established physical preparation practices, such as football. However, it remains unclear whether menstrual cycle phases and oral contraceptive (OC) use influence the force-velocity profile. The aim of this study was to determine whether squat jump and sprint force-velocity profiles change throughout the menstrual cycle or during the use of OC in elite female football players.